Oxidation of an Oligonucleotide-Bound Ce-III/Multiphosphonate Complex for Site-Selective DNA Scission - Lonnberg T; Aiba Y; Hamano Y; Miyajima Y; Sumaoka J; Komiyama M (WILEY-BLACKWELL, 2022)
Oligodeoxyribonucleotide conjugates of ethylenediamine-N,N,N',N'-tetrakis(methylenephosphonic acid) (EDTP) have been used to place a Ce-III/EDTP complex in close proximity to predetermined phosphodiester linkages of a complementary target oligonucleotide. In the presence of atmospheric oxygen, the Ce-III is oxidized into Ce-IV which, in turn, efficiently cleaves the target phosphodiester linkage. No cleavage occurs at the other single-stranded regions, which suggests that the catalytic Ce species is strictly localized next to the target phosphodiester linkage. No decrease in the reaction rate is observed upon introduction of scavengers for hydroxyl radicals (such as DMSO or MeOH) or singlet oxygen (such as NaN3) to the system; this indicates that the reaction proceeds via a hydrolytic pathway. Any significant contribution by an oxidative pathway is further ruled out by the observation that nucleosides remain intact after incubation with Ce-IV/EDTP complex for extended periods.